Improvement Sistem Rekrutmen Karyawan PT Ecogreen Oleochemicals (Batam Plant) - Gunawan, Timothy Calvin; Rahardjo, Jani (Jurnal Titra, 2014)
In nowadays, PT. Ecogreen Oleochemicals Batam requires an effective and efficient recruitment system to select new employees. The existing recruitment system does not yet have a test that can measure the ability of prospective employees. This company planned to acquire an additional process in the system of recruitment of employees, namely General Aptitude Test (GAT). General aptitude Test have 2 types of test for level Supervisor and Rank and File. The Supervisor has 5 types of test such as Sequences, Perceptual, Analysis, Number Skills and Dynamics. Rank and File have 3 types of tests which are Perceptual, Analysis and Number Skills. The test results obtained by testing the lowest average value was 32.9 then set for a minimum of 30 passing for all types of tests. Only dynamics test that has a correlation between GAT and Performance values.